2023
DOI: 10.3390/photonics10010092
|View full text |Cite
|
Sign up to set email alerts
|

High-Sensitivity Temperature Sensor Based on the Perfect Metamaterial Absorber in the Terahertz Band

Abstract: In this study, a perfect metamaterial absorber (PMMA) based on an indium antimonide temperature-sensitive material is designed and investigated in the terahertz region. We demonstrate that it is an ideal perfect narrow-band absorber with polarization-insensitive and wide-angle absorption properties. Numerical simulation results show that the proposed PMMA can be operated as a temperature sensor with a sensitivity of 21.9 GHz/K. A graphene layer was added to the PMMA structure to improve the sensitivity, and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…This is because of the increase in the equivalent inductance and capacitance of the proposed sensor as the stripe width increases. Accordingly, the resonance frequency decreases [29], [51]. In Fig.…”
Section: Sensitivity Analysis For Cancer Early Detectionmentioning
confidence: 83%
See 3 more Smart Citations
“…This is because of the increase in the equivalent inductance and capacitance of the proposed sensor as the stripe width increases. Accordingly, the resonance frequency decreases [29], [51]. In Fig.…”
Section: Sensitivity Analysis For Cancer Early Detectionmentioning
confidence: 83%
“…As the dielectric layer thickness h increases the equivalent inductance of the polyimide layer should be increased which decreases the equivalent capacitance between the two metallic plates. Whereas the decrease in the equivalent capacitance is somewhat less than the increase in the inductance, as a result, a decrease in the resonant frequency is obtained [56]. Further according to the transmission phase relation reported in [57]: (7) where εr and λ are the dielectric constant and wavelength, respectively.…”
Section: Sensitivity Analysis For Cancer Early Detectionmentioning
confidence: 95%
See 2 more Smart Citations
“…In the last few years, the majority of research on metamaterials has focused on achieving a single function. For example, Wang et al [14] innovatively crafted a metamaterial using indium antimonide temperature-sensitive material. Their research revealed it to be a game-changing narrowband absorber, exhibiting both polarization insensitivity and broad-angle absorption.…”
Section: Introductionmentioning
confidence: 99%